The impact of urban farming on environmental and community aspects in Sumurrejo Gunungpati village, Semarang - Fadhillah Fadhillah; Rizki Wulan Maharani; Rizki Nur Ardani; Widya Eka Lutfiah Ningrum (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2024)
In Sumurrejo village, Gunungpati district, Semarang, urban farming has begun to develop in response to the need for local food and better environmental quality. Through this study, it is hoped that a deeper understanding will be gained regarding how urban farming can contribute to better environmental management and the formation of more connected communities through sustainable agricultural practices. This research uses qualitative data and inductive analysis, namely an analysis based on the data obtained, then developing specific relationship patterns or hypotheses. This research provides an understanding that urban farming has many positive impacts, one of which is in the environmental aspect of society.